Punção aspirativa por agulha fina em lesão nodular de tireóide - Bezerra, Carlos Felipe Saraiva; Oliveira, Luiz Roberto De; Gomes, Teresa Neuma Albuquerque; Bezerra Filho, José Gomes [UNESP]; Andrade Neto, José Moacyr; Pierre Filho, Paulo De Tarso Ponte (Colégio Brasileiro de Cirurgiões, 2003)
BACKGROUND: The objective of this study is to analyze the accuracy of fine-needle aspiration technique (FNA) in patients who presented thyroid nodular disease referred to the Surgical Department of the Ceará Federal University School of Medicine. METHODS: One hundred and thirty patients with palpable thyroid nodules were operated on for thyroidectomy, based on clinical and cytological criteria. FNA was performed with disposable 10-ml syringes, 25x06 disposable needles, microscopy blades, blade bottles and 95% alcohol. Cytological and histological results were compared. RESULTS: Cytological analysis were grouped as: benign - 58 (44,6%), undetermined - 38 (29,2%), malignant - 21 (16,2%) and inadequate - 13 (10,0%). Histology showed 45 malignant lesions and 85 benign nodules. Comparison between cytology and histology results enabled us to obtain the following indicators: sensitivity - 74%, specificity - 98%, predictive positive value - 95,2%, false-positive - 1,9%, predictive negative value - 87,9%, false-negative - 25,9% and accuracy - 89,8%. If the undetermined results (suspicious of being malignant and follicular disease) were considered as being positive to malignancy, the indicators were 82,5%; 66,2%; 55,9%; 33,7%; 87,9%; 17,5% e 71,8% respectively. Evaluation of the groups mentioned showed statistical significance by Fisher's Test. CONCLUSIONS: The results confirm the accuracy of FNA in the management of patients with nodular thyroid disease at University Hospital Walter Cantídio of Ceará Federal University School of Medicine.

OBJETIVO: O presente trabalho se propõe a analisar a precisão da punção aspirativa por agulha fina (PAAF) em pacientes avaliados no Departamento de Cirurgia do Hospital Universitário Walter Cantídio (HUWC), portadores de lesões nodulares da tireóide. MÉTODO: A avaliação contemplou 130 pacientes que apresentavam nódulos de tireóide clinicamente palpáveis, com indicação de tratamento cirúrgico, segundo critérios clínicos e citopatológicos. Utilizaram-se seringas descartáveis de 10ml, agulhas descartáveis 25x06, lâminas esmerilhadas para microscopia, frascos para lâmina e álcool a 95%. RESULTADOS: A análise citopatológica mostrou nódulos benignos - 58 (44,6%); indeterminados (lesões foliculares e suspeitos) - 38 (29,2%); malignos - 21 (16,2%) e insatisfatório - 13 (10,0%). Através do exame histopatológico, foram identificadas 45 neoplasias malignas e 85 lesões benignas. Foram observados os seguintes índices na análise da associação entre os dados obtidos com citopatologia e histopatologia: sensibilidade de 74%; especificidade de 98%; valor preditivo positivo de 95,2%; falso-positivo de 1,9%; valor preditivo negativo de 87,9%; falso-negativo de 25,9% e acurácia de 89,8%. Quando foram incluídos os resultados indeterminados (suspeito e lesão folicular) como positivo para neoplasia maligna, na mesma seqüência anterior, os resultados foram: 82,5%; 66,2%; 55,9%; 33,7%; 87,9%; 17,5% e 71,8%. A avaliação dos grupos supracitados mostrou significância estatística (p = 0,00), aplicando-se o teste exato de Fisher. CONCLUSÕES: Os resultados apresentados confirmam a precisão da PAAF na abordagem dos pacientes com lesões nodulares da tireóide, no HUWC-UFC.
Fine-needle aspiration in thyroid nodular disease
Keywords: Goiter; Thyroid nodule; Neoplasms; Thyroidectomy; Biopsy; needle; Bócio; Nódulo da glândula tireóide; Neoplasias; Tireoidectomia; Biópsia por agulha